'Special' non-human actors in the 'inclusive' early childhood classroom: The wrist band, the lock and the scooter board. Issue 3 (September 2015) - Watson, Karen; Millei, Zsuzsa; Petersen, Eva Bendix
It is well established in research that early childhood classrooms are one of the most controlled environments during the human life course. When control is discussed, the enactment of regulatory frameworks and various discourses are analysed but less focus is paid on the materialities of classrooms. In this article, we pay attention to 'special' non-human actors present in an 'inclusive' early childhood classroom. These 'special' non-human actors are so named as they operate in the classroom as objects specific for the child with a diagnosis. The 'special' non-human actors, in the specific case the wrist band, the lock and the scooter board, take on meaning within discourses in the 'inclusive' classroom. We illuminate how these non-human actors contribute to the constitution of the 'normal' and the regulation of educators and children. To trouble the working of power and the control these objects effect on all who is present in the classroom, we ask the following questions: What do these non-human actors do in the 'inclusive' classroom and with what effects? How do non-human actors reproduce/produce the 'normal', impossible/possible ways to be and act, thus control educators and children? The data used in our analyses were produced as part of a 6-month-long ethnographic engagement in three early childhood settings in the broader region of Newcastle, Australia. It includes observations and conversations with children.